No effect of test and treat on sexual behaviours at population level in rural South Africa. (15th March 2019) - Rolland, Matthieu; McGrath, Nuala; Tiendrebeogo, Thierry; Larmarange, Joseph; Pillay, Deenan; Dabis, François; Orne-Gliemann, Joanna
Abstract : Context: Within the community-randomized ANRS 12249 Treatment-as-Prevention trial conducted in rural South Africa, we analysed sexual behaviours stratified by sex over time, comparing immediate antiretroviral therapy irrespective of CD4 + cell count vs. CD4 + -guided antiretroviral therapy (start at CD4 +  cell count > 350 cells/μl then >500 cells/μl) arms. Methods: As part of the 6-monthly home-based trial rounds, a sexual behaviour individual questionnaire was administered to all residents at least 16 years. We considered seven indicators: sexual intercourse in the past month; at least one regular sexual partner in the past 6 months; at least one casual sexual partner in the past 6 months and more than one sexual partner in the past 6 months; condom use at last sex (CLS) with regular partner, CLS with casual partner, and point prevalence estimate of concurrency. We conducted repeated cross-sectional analyses, stratified by sex. Generalized Estimating Equations models were used, including trial arm, trial time, calendar time and interaction between trial arm and trial time. Results: CLS with regular partner varied between 29–51% and 23–46% for men and women, respectively, with significantly lower odds among women in the control vs. intervention arm by trial end ( P  < 0.001). CLS with casual partner among men showed a significant interaction between arm and trial round, with no consistent pattern. Women declared more than one partner in the past 6 months in less than 1% of individual questionnaires; among men, rates varied between 5–12%, and odds significantly and continuously declined between calendar rounds 1 and 7 [odds ratio = 4.2 (3.24–5.45)]. Conclusion: Universal Test and Treat was not associated with increased sexual risk behaviours. Abstract : Supplemental Digital Content is available in the text